2021
DOI: 10.1038/s41598-020-79654-8
|View full text |Cite
|
Sign up to set email alerts
|

Linker histone defines structure and self-association behaviour of the 177 bp human chromatosome

Abstract: Linker histones play essential roles in the regulation and maintenance of the dynamic chromatin structure of higher eukaryotes. The influence of human histone H1.0 on the nucleosome structure and biophysical properties of the resulting chromatosome were investigated and compared with the 177-bp nucleosome using Cryo-EM and SAXS. The 4.5 Å Cryo-EM chromatosome structure showed that the linker histone binds at the nucleosome dyad interacting with both linker DNA arms but in a tilted manner leaning towards one of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(15 citation statements)
references
References 100 publications
(161 reference statements)
1
12
0
Order By: Relevance
“…Previous studies on dense phases of nucleosomes demonstrated formation of highly ordered structures consisting of columns of stacked nucleosomes ( Allahverdi et al, 2011 ; Berezhnoy et al, 2016 ; Bertin et al, 2007b ; Eltsov et al, 2018 ; Korolev et al, 2012 ; Leforestier and Livolant, 1997 ; Livolant et al, 2006 ; Mangenot et al, 2003a , b ). For the isotropic columnar phase, SAXS scattering curves showed three broad scattering peaks corresponding to (i) the average intercolumnar distance, typically at q * =~ 0.065, with q * decreasing as the linker DNA increases ( Mangenot et al, 2003b ; Wang et al, 2021 ), (ii) the stacking distance between nucleosomes in a column (typically at q * =~ 0.11), and (iii) the form factor of the column ( Livolant et al, 2006 ). In a highly ordered columnar phase, such as obtained from Mg 2+ -induced precipitation of nucleosome core particles, these peaks appear sharp and well-resolved ( Berezhnoy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies on dense phases of nucleosomes demonstrated formation of highly ordered structures consisting of columns of stacked nucleosomes ( Allahverdi et al, 2011 ; Berezhnoy et al, 2016 ; Bertin et al, 2007b ; Eltsov et al, 2018 ; Korolev et al, 2012 ; Leforestier and Livolant, 1997 ; Livolant et al, 2006 ; Mangenot et al, 2003a , b ). For the isotropic columnar phase, SAXS scattering curves showed three broad scattering peaks corresponding to (i) the average intercolumnar distance, typically at q * =~ 0.065, with q * decreasing as the linker DNA increases ( Mangenot et al, 2003b ; Wang et al, 2021 ), (ii) the stacking distance between nucleosomes in a column (typically at q * =~ 0.11), and (iii) the form factor of the column ( Livolant et al, 2006 ). In a highly ordered columnar phase, such as obtained from Mg 2+ -induced precipitation of nucleosome core particles, these peaks appear sharp and well-resolved ( Berezhnoy et al, 2016 ).…”
Section: Discussionmentioning
confidence: 99%
“…It is generally accepted that linker histones bind to the nucleosome and protect an extra 20 bp of linker DNA. Many explanations have been proposed to describe the location of the linker histones, or linker histone globular domains, within the nucleosome, their interaction and chromatosome protection through biochemical analysis, structural studies or computing simulations [ 9 , 36 , 37 , 38 , 39 , 40 , 57 , 62 , 63 , 64 , 65 , 66 , 67 ]. The current study is the first in vitro analysis of chromatosomal DNA extensions protected by linker histones or linker histone globular domains, in the context of a long-range nucleosome array formed on a natural genomic DNA sequence.…”
Section: Discussionmentioning
confidence: 99%
“…They form a repetitive structure (beads on a string) that results in chromatin fiber [ 4 ]. The winged-helix domain (WHD) of histone H1 [ 5 ] also binds close to the entry and exit sites of DNA in the nucleosome [ 6 , 7 , 8 ], and this binding plays a critical role in the modulation of the chromatin fiber folding [ 9 ]. Both ‘core histones’ and ‘linker histones’ consist of a bipartite/tripartite protein organization in which an N-terminal intrinsically disordered domain (IDD) [ 10 ] flanks a structured domain WHD [ 11 ] for linker histones or a histone fold domain (HFD) [ 12 ] for core histones.…”
Section: Chromatin and Epigenetics: A Brief Overviewmentioning
confidence: 99%